Glowworm Swarm Optimization based Clustered on – Demand Load Balancing Scheme (GSO-COD-LBS) for Heterogeneous Mobile Ad hoc Networks - P, Aruna Devi; K, Karthikeyan (International Journal of Computer Sciences and Engineering, 2019)
Obtaining quality of service (QoS) through several routing schemes attracts researchers in the field of MANETs. Optimized routing through energy aware load balanced schemes is plays a significant role in ensuring QoS as well as many real – time applications. In this phase of research work, Glowworm Swarm Optimization is used for performing clustering operation. An adaptive on – demand routing mechanism is also employed. Simulation settings are used for analyzing the performance of the GSO-COD-LBS with other routing protocols / solutions / schemes using the metrics packet delivery ratio, throughput, packets drop, overhead and delay. From the results that are obtained through simulations it is inferred that GSO-COD-LBS outperforms other existing routing protocols and our earlier proposed works.